Constraints on the size and temperature of magma batches that constructed the Peninsula pluton, based on the metamorphic record of metasedimentary xenoliths - Muller, Jared (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.